Whose hands are these? : a community helper guessing book - Paul, Miranda (Minneapolis, Minn. : Millbrook Press, 2016)
Lively rhyming clues introduce various jobs that hands can do from cooking pizza to bandaging a scraped knee, and prompt readers to guess which community helpers are being portrayed.
Ages 4-9.
Keywords: Occupations -- Juvenile literature; Helping behavior -- Juvenile literature; Occupations; Helpfulness